Analisis Ketersediaan Bahan Baku Industri Tahu dan Tempe melalui Pendekatan Supply Chain Management: Analysis of Raw Material Availability of Tofu and Tempeh Industry through Supply Chain Management Approach - Handayani, Yuni; Tanggasari, Devi (Jurnal Teknologi dan Mutu Pangan, 2024)
Supply Chain Management (SCM) is a crucial component in the manufacturing industry. SCM involves key activities such as designing new products, planning production and inventory, executing production, shipping activities, and procuring raw materials, especially at UD. Rahayu. UD. Rahayu is a culinary business specializing in tofu and tempeh, operating since 1980 and continuing to date. The business has consumers in various places. During the red months (when the sky is bright), UD. Rahayu reduces its production, impacting the production process and raw material availability at UD. Rahayu. The objective of this research is to examine Supply Chain Management and the distribution patterns of raw materials for tofu and tempeh from local suppliers at UD. Rahayu. The research was conducted using qualitative methods, including observation, in-depth interviews, and the distribution of questionnaires to relevant parties involved in the study, containing pertinent questions. The results indicate that the inventory risk of raw materials is not solely due to a lack of suppliers; several factors influence it, such as the risk of damaged raw materials, mismatched specifications, delayed arrival of raw materials, and excess raw material risk. Consequently, the success of a supply chain, particularly in the availability of raw materials, can have a positive impact on meeting the production needs of UD. Rahayu. This research makes an important contribution to our understanding of Supply Chain Management in the context of culinary businesses, as well as providing a basis for further research in this area.